2021
DOI: 10.21037/jtd-20-1580
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory parameters and pulmonary biomarkers in smokers with and without chronic obstructive pulmonary disease (COPD)

Abstract: Background: We organized this study in order to investigate differences in serum inflammatory profiles and circulating serum pneumoproteins between smokers with and without chronic obstructive pulmonary disease (COPD). Methods: Patients aged 35-70 years with COPD and a smoking history ≥10 pack-years (cases, n=38) and 38 participants with the same smoking history without COPD (controls) were included in a comparative study conducted as part of a population-based cross-sectional study with 2,388 individuals in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Asthma may contribute less significantly to systemic inflammation due to the short onset of episodes of acute asthma attacks. Previous studies indicated that COPD significantly increases the systemic inflammatory burden, which could be further amplified by smoking (Qian et al, 2020;Andreeva et al, 2021). Smoking is a well-known risk factor for COPD and heart disease, as well as tooth loss (Cunningham et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Asthma may contribute less significantly to systemic inflammation due to the short onset of episodes of acute asthma attacks. Previous studies indicated that COPD significantly increases the systemic inflammatory burden, which could be further amplified by smoking (Qian et al, 2020;Andreeva et al, 2021). Smoking is a well-known risk factor for COPD and heart disease, as well as tooth loss (Cunningham et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, particularly alveolar macrophages, are the most abundant type of immune cell seem to accumulate in areas of tissue damage in the lungs 3 . This increase in the number of macrophages may be due to active recruitment of circulating monocytes as a result of the chemoattractant actions of CCL2 and CXCL1 22,23 . CXCL8 concentrations are also increased in induced sputum of patients with COPD and increase further during exacerbations 22,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…This increase in the number of macrophages may be due to active recruitment of circulating monocytes as a result of the chemoattractant actions of CCL2 and CXCL1 22,23 . CXCL8 concentrations are also increased in induced sputum of patients with COPD and increase further during exacerbations 22,24,25 . CXCL8 is secreted from macrophages, T cells, epithelial cells, and neutrophils and is chemotactic for neutrophils 26,27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, statins inhibit thrombotic responses ( 4 - 6 ). Statins have anti-inflammatory and immunomodulatory effects, which can reduce the levels of inflammatory markers [such as C-reactive protein (CRP)] in the serum, improve vascular endothelial function, reduce the infiltration and adhesion of inflammatory cells, and inhibit the production of inflammatory factors such as tumor necrosis factor α (TNF-α) and interleukin-6 (IL-6) ( 7 , 8 ). Studies have shown that statins attenuate the progression of PH in several animal models ( 9 - 11 ).…”
Section: Introductionmentioning
confidence: 99%